Pembuatan Website untuk Mesin Penjualan Otomatis di Central New Jersey - Atfinia, Neiska Syifa; Nurhayati, Siti Fatimah (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Vending machine sales is a system designed to replace human labor, from product offerings, order processing, to payment transactions. This study is to create an easily accessible sales platform, customers can make purchases on this website at any time because it can be accessed from various devices such as computers, laptops, tablet PCs, and smartphones. Website creation includes the process of designing, developing and maintaining a website that functions as an online platform. This website involves a variety of skills ranging from graphic design to programming. The results of this study indicate that the creation of a website that can be accessed at any time, without time limits and allows customers to make purchases according to their needs without having to be tied to certain operating hours. This is in line with the growing need for digitalization and automation of food and beverage product purchasing services.
Keywords: Central New Jersey; Vending Machine Sales; Website